Carbon footprint and architecture firms: a case study approach for mitigation - Poudyal, Dikshya (Kansas State University, 2014)
Almost forty percent of the global energy use and one-third of the global greenhouse gas emission comes from the building industry. Thus, this sector has the largest potential for delivering long term substantial greenhouse gas reduction. (UNEP, 2009)This dissertation starts with the energy auditing of an architectural firm to calculate the amount of energy used. It then expands into addressing the issue on a greater perspective. The whole agenda of the thesis was to develop a strategy to include the building industry in global carbon market. This thesis was performed in collaboration with nationally recognized, medium-sized mid-western architecture firm. A yearlong internship was completed under this firm, and collaborative research was carried out. To reduce the carbon dioxide emission, it is crucial to be able to measure it. This thesis aims at creating basic guidelines for architecture firms to mitigate its carbon footprint. It also examines the possibilities of carbon footprint mitigation on a bigger scale by proposing a system that would encourage architectural and engineering firms to design and produce more energy efficient buildings. The proposed system deals with calculation and incorporation of creative handprint of an architectural firm and uses the system to rebate its carbon footprint and convert the surplus handprint to a credit in the carbon market. The argument made here is that this scheme is driven by incentives and encourages more architecture and engineering firms to design sustainable buildings. The final proposal links the entire building industry to the carbon market. The proposal made is that a positive handprint of architecture and engineering firms can be converted to carbon credits and traded in the carbon markets.
Keywords: Carbon footprint; Building industry; Sustainable; Sustainability (0640)